The Reformulation of Dakwah Science and its Parts - Syukriadi sambas (Universitas Islam Negeri Imam Bonjol Padang, 2005)
Nowadays Islamic Dakweh has existed as a part of Islamic Studies. But, t was not clear enough how this science was buit or structured.This article answers theproblems of Dakwah structure asa part of Islamic Sciences, from its ontologic,epistemologic and axiologic point of view